Anatomical description of the vessels arterial carotid-cerebral in domestic chicken Gallus gallus Linnaeus (Aves: Galliformes: Phasianidae). - Verduzco Mendoza, Antonio; Arch Tirado, Emilio; Contreras Figueroa, María Elena; Leybón Ibarra, Jaime; Alfaro Rodríguez, Alfonso; Licona Bonilla, Juan (Instituto de Ecología, A.C., 2009)
We describe the carotid-cerebral arterial vasculature of the domestic rooster (Gallus gallus Linnaeus). Ten cocks race Rhode Island of 2.5 kg of weight were used, which were subjected to vascular replesion conservation technique. It was concluded that anastomosis intercarotidea, the formation of the basilar artery and the absence of the vertebral arteries are the most significant components of the cephalic vasculature. It is proposed to standardize the nomenclature of the arteries of the brain-stem carotid arterial because of the confusing terminology used by various authors